Integrating media clusters and value networks: Insights for management theory and research from a case study of Mediapolis in Finland. (16th December 2016) - Virta, Sari; Lowe, Gregory Ferrell
Abstract: We argue that there is scholarly potential in linking theory on industry clusters with theory on value networks. To date, these two theoretical streams have developed largely in parallel, limiting understanding of how the two are integrated in practice. By considering these theories in combination and the unique context of creative industries, we generate insight on the management of clusters as value networks. Our ongoing longitudinal empirical case is a new media cluster called 'Mediapolis' in the city of Tampere, Finland. The case study commenced at the time the cluster was in the planning and early operational stage. Results demonstrate the usefulness of linking the two theories, and support a future research agenda examining the types of cluster configurations meeting the criteria of value networks, and the conditions under which value network cluster configurations are more sustainable than simply a spatial agglomeration of clusters.